Transcatheter tricuspid valve interventions: Current status and future perspectives - Alperi, Alberto; Almendárez, Marcel; Álvarez, Rut; Moris, Cesar; Leon, Victor; Silva, Iria; Hernández-Vaquero, Daniel; Pascual, Isaac; Avanzas, Pablo (Frontiers in Cardiovascular Medicine, 2022)
The development of transcatheter therapies to treat valvular heart diseases has changed the rules of the game, particularly in the case of aortic stenosis and mitral regurgiutation. In the last years, the tricuspid valve has also been the focus of these percutaneous techniques for several reasons: 1) tricuspid regurgitation is a frequent disease associated with poor clinical outcomes in spite of medical tratment, leading to end-stage right ventricular heart failure, 2) surgical tricuspid valve repair or replacement has been the treatment of choice for patients with tricuspid valve disease, but high mortality rates for isolated surgical tricuspid valve intervention have been reported in the literature and 3) most patients with tricuspid pathology are ultimately denied cardiac surgery because of their comorbidity burden. Thus, in this context the development of less invasive catheter-based therapies would be of high clinical relevance. The present review provides an overview regarding the framework of chronic tricuspid regurgitation transcatheter therapeutic options, summarizes the transcatheter systems under clinical use or clinical evaluation with their technical features, and describes the updated current evidence in this challenging and evolving field.